Zoonotic and reverse zoonotic events of SARS-CoV-2 and their impact on global health. Issue 1 (1st January 2020) - Munir, Khalid; Ashraf, Shoaib; Munir, Isra; Khalid, Hamna; Muneer, Mohammad Akram; Mukhtar, Noreen; Amin, Shahid; Ashraf, Sohaib; Imran, Muhammad Ahmad; Chaudhry, Umer; Zaheer, Muhammad Usman; Arshad, Maria; et al.
ABSTRACT: Coronaviruses (CoVs) are enveloped, positive sense, single-stranded RNA viruses. The viruses have adapted to infect a large number of animal species, ranging from bats to camels. At present, seven CoVs infect humans, of which Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is responsible for causing the Coronavirus Disease 2019 (COVID-19) in humans. Since its emergence in late 2019, SARS-CoV-2 has spread rapidly across the globe. Healthcare systems around the globe have been stretched beyond their limits posing new challenges to emergency healthcare services and critical care. The outbreak continues to jeopardize human health, social life and economy. All known human CoVs have zoonotic origins. Recent detection of SARS-CoV-2 in pet, zoo and certain farm animals has highlighted its potential for reverse zoonosis. This scenario is particularly alarming, since these animals could be potential reservoirs for secondary zoonotic infections. In this article, we highlight interspecies SARS-CoV-2 infections and focus on the reverse zoonotic potential of this virus. We also emphasize the importance of potential secondary zoonotic events and the One-Health and One-World approach to tackle such future pandemics.